RELIGIÃO E SAÚDE: UM ESTUDO SOBRE A UMBANDA EM SÃO BERNARDO DO CAMPO - Jesus, Edmar Antonio de (2012)
The theme of this research is the relation between Health and Umbanda in Sao Bernardo do Campo, which is based on two Umbanda temples, one in Rudge Ramos and one in Vila Rosa. The first is situated in a medium-high society region, and the second, in a medium society region. We stated that even in a post-modern society, with so many advances in science, techniques and traditional medicine, men and women turn to religion for answers to questions they cannot give. Religion has been a place where they are trying to find answers when it comes to health recovery. Umbanda has been one of the religious segments to which men and women present their requests, in hopes to obtain an effective answer. After our observation in rituals of cure practice , questionnaire applications and interviews with people who frequent the temples and mediums from both temples, many people said to be cured from their diseases. However, even with all excellence of Orixas in manipulating umbandists therapeutical practices, they go along with traditional medicine. It is intriguing how men and women, living on a large city, conceal a comprehension of health and disease, where, apparently, religion and science do not mix.